Exploring the perspectives and practices of humanitarian actors towards the Participation Revolution in humanitarian digital health responses: a qualitative study - Jennifer Benson; Meret Lakeberg; Tilman Brand (BMC, 2024)
Abstract Background As crises escalate worldwide, there is an increasing demand for innovative solutions to enhance humanitarian outcomes. Within this landscape, digital health tools have emerged as promising solutions to tackle certain health challenges. The integration of digital health tools within the international humanitarian system provides an opportunity to reflect upon the system's paternalistic tendencies, driven largely by Global North organisations, that perpetuate existing inequities in the Global South, where the majority of crises occur. The Participation Revolution, a fundamental pillar of the Localisation Agenda, seeks to address these inequities by advocating for greater participation from crisis-affected people in response efforts. Despite being widely accepted as a best practice; a gap remains between the rhetoric and practice of participation in humanitarian response efforts. This study explores the extent and nature of participatory action within contemporary humanitarian digital health projects, highlighting participatory barriers and tensions and offering potential solutions to bridge the participation gap to enhance transformative change in humanitarian response efforts. Methods Sixteen qualitative interviews were conducted with humanitarian health practitioners and experts to retrospectively explored participatory practices within their digital health projects. The interviews were structured and analysed according to the Localisation Performance Measurement Framework's participation indicators and thematically, following the Framework Method. The study was guided by the COREQ checklist for quality reporting. Results Varied participatory formats, including focus groups and interviews, demonstrated modest progress towards participation indicators. However, the extent of influence and power held by crisis-affected people during participation remained limited in terms of breadth and depth. Participatory barriers emerged under four key themes: project processes, health evidence, technology infrastructure and the crisis context. Lessons for leveraging participatory digital health humanitarian interventions were conducting thorough pre-project assessments and maintaining engagement with crisis-affected populations throughout and after humanitarian action. Conclusion The emerging barriers were instrumental in shaping the limited participatory reality and have implications: Failing to engage crisis-affected people risks perpetuating inequalities and causing harm. To advance the Participation Revolution for humanitarian digital health response efforts, the major participatory barriers should be addressed to improve humanitarian efficiency and digital health efficacy and uphold the rights of crisis-affected people.